Estudo de fluxos turbulentos acima da baía de Caxiuanã, na Amazônia oriental - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2008)
The turbulent exchanges between Caxiuanã Bay and the atmosphere during the COBRA - Pará Experiment (Nov/2006) are investigated. Two methods were used to estimate the fluxes: the covariance method (MC), which uses low frequency information from the region of turbulent kinetic energy production, and the Dissipative - Inertial method (MOI), which uses high frequency information contained in the inertial subdomain of the power spectra of the turbulent quantities. The MC is considered to be the standard procedure. However, the issue of calculating turbulent flow is complex and its exact determination is still controversial. In Amazonia the calculation of the flows is commonly aggravated by the non-stationarity of the turbulent signal, in addition to other problems. One of the difficulties associated with the calculation of flow by MC refers to the need to have stationary data for a relatively long period (at least half an hour) in order to enable the estimation of the covariance between vertical velocity (w') and scalars in a statistically robust manner. An alternative to overcome this difficulty is the use of the Dissipative - Inertial Method (MOI). The main objective of this work was to estimate turbulent fluxes using two different methods, MC and MOI, and to compare them. The data were collected in a water tower installed over the Caxiuanã bay. The results show that the sensible heat flux (H) above Caxiuanã Bay is always positive and that there is agreement between the values calculated by the two methods (MC and MDI), with correlation coefficients equal to r = 0.73 and r = 0.60 for H and for the stability parameter (ce), respectively. Furthermore, a positive jump in the sign of H was observed between 7 pm and 10 pm, which is a scientifically interesting result. The CO) fluxes above Caxiuanã bay were always positive (fluxes from water to atmosphere), indicating constant CO) release from the bay to the atmosphere, which can be attributed to the action of decomposing organic matter near the shore where the measurements were taken. The Bowen ratio showed low values, less than 0.25 lower than those found above the Caxiuanã forest, which were in the order of 0.4. Thus, the results validate the calculation of turbulent fluxes above the bay of Caxiuanã, by the Dissipative-Inertial Method (MDI).
Study of turbulent flows above Caxiuanã Bay, Eastern Amazonia
Keywords: Fluxos turbulentos; Baía de Caxiuanã; Método das covariâncias; Método dissipativo-inercial; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS